The alkylating carcinogen N-methyl-N'-nitro-N-nitrosoguanidine activates the plasminogen activator inhibitor-1 gene through sequential phosphorylation of p53 by ATM and ATR kinases - Vidal, Berta; Parra, Maribel; Jardí, Mercè; Saito, Shin'ichi; Appella, Ettore; Muñoz-Cánoves, Pura (Thrombosis and haemostasis, 2005)
The alkylating agent MNNG is an environmental carcinogen that causes DNA lesions leading to cell death. We previously demonstrated that MNNG induced the transcriptional activity of the plasminogen activator inhibitor-1 (PAI-1) gene in a p53-dependent manner. However, the mechanism(s) linking external MNNG stimulation and PAI-1 gene induction remained to be elucidated. Here, we show that ATM and ATR kinases, but not DNA-PK, which participate in DNA damage-activated checkpoints, regulate the phosphorylation of p53 at serine 15 in response to MNNG cell treatment. Using ATM-deficient cells, ATM was shown to be required for early phosphorylation of serine 15 in response to MNNG, whereas catalytically inactive ATR selectively interfered with late phase serine 15 phosphorylation. In contrast, DNA-PK-deficient cells showed no change in the MNNG-induced serine 15 phosphorylation pattern. In agreement with this, sequential activation of ATM and ATR kinases was also required for adequate induction of the endogenous PAI-1 gene by MNNG. Finally, we showed that cells derived from PAI-1-deficient mice were more resistant to MNNG-induced cell death than normal cells, suggesting that p53-dependent PAI-1 expression partially mediated this effect. Since PAI-1 is involved in the control of tumor invasiveness, our finding that MNNG induces PAI-1 gene expression via ATM/ATR-mediated phosphorylation of p53 sheds new insight on the role of these DNA damage-induced cell cycle checkpoint kinases.